Tillage practices influence on growth, yield and economics of Toria (Brassica rapa var. Toria) under rainfed condition of Chhattisgarh (Journal of Oilseed Brassica, 2026)
An experiment was conducted to study the effect of tillage practices on growth and productivity of toria, with 4 tillage practices viz. T1- Zero tillage direct drilling of seeds and fertilizers at 2nd days after harvesting of rice, T2 -Minimum tillage and line sowing of seeds at 3rd days after harvesting of rice, T3-Minimum tillage at 6th days after harvesting of rice, T4-Farmer practice broadcasting seeds and fertilizer at 12th days after harvesting of rice. The plant population m2 (47.4), plant height (99.44 cm), branches plant-1 (1.6), dry biomass (2.8 g plant-1), number of siliqua plant-1 (28.4), number of seeds siliqua-1 (9.7), pod length (4.7 cm), seed yield (4.3 q ha-1) and stover yield (12.2 q ha-1) was recorded significantly higher under T2 (Minimum tillage and line sowing of seed at 3rd DAH of rice), but these are found statistically similar with T1 (Zero tillage direct drilling of seeds at 2nd DAH of rice). Whereas, test weight (g) and harvest index (%) did not vary significantly by different tillage practices. The gross returns (Rs. 13330 ha-1) was highest in treatment T2, but net return (Rs. 3908 ha-1) and B:C (1.42) ratio were higher in the T1. In conclusion the minimum tillage and line sowing of seeds at 3rd days after harvesting of rice and/or Zero tillage direct drilling of seeds and fertilizers at 2nd days after harvesting of rice were the better tillage practice as it performed well over the remaining treatments with respect to all growth, yield and economics of toria grown under rainfed conditions of Chhattisgarh.